The transcription factor Bcl11a is essential for B-1a cell maintenance during aging - Shasha Xu; Liangfeng Huang; Xingjie Liu; Linlin Zhang; Jing Wang; Yifeng Hu; Yi Yang; Xiaojie Shi; Chaohong Liu; Rong Wang; Zhichao Miao; Yong Yu (Proceedings of the National Academy of Sciences, 2025)
B-1a cells, a self-renewing B cell subset essential for innate immunity, produce natural IgM antibodies that defend against pathogens, yet mechanisms sustaining their maintenance during aging remain unclear. We report that aging B-1a cells exhibit hallmarks of decline, including DNA damage, apoptosis, and reduced proliferation, with striking sex-specific disparities: aged females retain higher B-1a cell numbers than males, correlating with enhanced glycolysis and chromatin accessibility. Motif analysis of accessible regions identified the transcription factor Bcl11a, which shows elevated chromatin accessibility and expression in aged female B-1a cells but declines in males. Bcl11a deletion reduced B-1a cell numbers, impaired viability, and increased apoptosis across sexes and ages. Mechanistically, Bcl11a sustains survival by upregulating antiapoptotic genes ( Mcl1 , Mdm2 , and Mdm4 ) to suppress p53-mediated apoptosis, as evidenced by partial rescue of viability defects in Bcl11a-deficient B-1a cells upon p53 deletion. Conversely, Bcl11a overexpression or Bcl11a-high B-1a cells from aged Bcl11a -eGFP reporter mice enhanced stress resistance. These findings establish Bcl11a as a key regulator of B-1a cell maintenance during aging and reveal its role in mitigating sex-dimorphic immune decline through transcriptional control of survival pathways.